Effects of Erectile Dysfunction Drugs Use on T-Cells and Immune Markers on Men Who Have Sex with Men. Issue 3 (3rd July 2022) - Park, Jee Won; Arah, Onyebuchi A.; Martinez-Maza, Otoniel; Dobs, Adrian S.; Ho, Ken S.; Palella, Frank J.; Seaberg, Eric C.; Detels, Roger
Abstract: Objective: Examine prospective relationships between erectile dysfunction (ED) drugs and CD4 and CD8 T-cells, and immune markers among men who have sex with men (MSM). Methods: Data from Multicenter AIDS Cohort Study, an observational prospective cohort study, with semiannual follow-ups conducted in four U.S. centers from 1998 onwards was used. Marginal structural models using g-computation were fitted to estimate the mean differences for the effects of self-reported ED drug use on CD4 and CD8 T-cell outcomes and immune biomarkers. Results: Total of 1, 391 men with HIV (MWH) and 307 men without HIV (MWOH) was included. Baseline mean CD4 cell count among MWH and MWOH was 499.9 and 966.7 cells/μL, respectively. At baseline, 41.8% of MWH were virally suppressed. ED drug users reported a mean of 44.4 months of exposure to ED drugs. ED drug use was associated with increased CD4 cell outcomes among MWH but not MWOH. Mean differences in CD4 cell counts after 1 year of ED drug use was 57.6 cells/μL and increased to 117.7 after 10 years among MWH. CD8 counts were higher in ED drug users among MWH over 10 years than non-users; no consistent differences were found among MWOH. ED drug use appeared to reduce immune marker levels, such as IL-6 and increase markers, such as IL-10. We observed similar effects of ED drug use on biomarker levels among MWOH. Conclusion: Long-term use of ED drugs do not adversely affect immune function among MWH or MWOH. Future studies on the relationships between different types of ED drugs and effects on T-cell subtypes are warranted.